Tachykinin-3 Genes and Peptides Characterized in a Basal Teleost, the European Eel: Evolutionary Perspective and Pituitary Role - Campo, Aurora; Lafont, Anne-Gaëlle; Lefranc, Benjamin; Leprince, Jérôme; Tostivint, Hervé; Kamech, Nédia; Dufour, Sylvie; Rousseau, Karine (Frontiers in Endocrinology, 2018)
In mammals, neurokinin B (NKB) is a short peptide encoded by the gene tac3. It is involved in the brain control of reproduction by stimulating GnRH neurons, mainly via kisspeptin. We investigated tac3 genes and peptides in a basal teleost, the European eel, which shows an atypical blockade of the sexual maturation at a pre-pubertal stage. Two tac3 paralogous genes (tac3a and tac3b) were identified in the eel genome, each encoding two peptides (NKBa or b and NKB-related peptide NKB-RPa or b). Amino-acid sequence of eel NKBa is identical to human NKB, and the three others are novel peptide sequences. The four eel peptides present the characteristic C-terminal tachykinin sequence, as well as a similar alpha helix 3D structure. Tac3 genes were identified in silico in 52 species of vertebrates and a phylogeny analysis was performed on the predicted TAC3 pre-pro-peptide sequences. A synteny analysis was also done to further assess the evolutionary history of tac3 genes. Duplicated tac3 genes in teleosts likely result from the teleost-specific whole genome duplication (3R). Among teleosts, TAC3b precursor sequences are more divergent than TAC3a, and a loss of tac3b gene would have even occurred in some teleost lineages. NKB-RP peptide, encoded beside NKB by tac3 gene in actinopterygians and basal sarcopterygians, would have been lost in ancestral amniotes. Tissue distribution of eel tac3a and tac3b mRNAs showed major expression of both transcripts in the brain especially in the diencephalon, as analyzed by specific qPCRs. Human NKB has been tested in vitro on primary culture of eel pituitary cells. Human NKB dose-dependently inhibited the expression of lhβ, while having no effect on other glycoprotein hormone subunits (fshβ, tshβ, gpα) nor on gh. Human NKB also dose-dependently inhibited the expression of GnRH receptor (gnrh-r2). The four eel peptides have been synthesized and also tested in vitro. They all inhibited the expression of both lhβ and of gnrh-r2. This reveals a potential dual inhibitory role of the four peptides encoded by the two tac3 genes in eel reproduction, exerted at the pituitary level on both LH and GnRH receptor.